Develop Speaking Skills with the Help of Modern Technology - Matenova F.M. (Euro Asian Journal Publishing, 2024)
The technology brought revolutionary changes in language usage. Technology is actively used in educational sectors rather than trade and transactions. It is the mode of communication. In order to communicate, speaking skills has to be excelled by the learners in learning English. In the fast developing 21st century various innovative technologies are being introduced to teach speaking skills in the classrooms. The present world is driven by technology, which cannot be denied. It is the means to get access with this modernized world. Though technology cannot play the crucial role of a teacher, it can be used as a additional tool for improving teaching methods in classroom. Internet, podcasts, video conferencing, videos and speech recognition software, TELL, Blogging are considered to be some of the best tools for teaching speaking skills. This paper aims to discuss some modern technologies available for teachers of English today to enhance speaking skill ofsecond orforeign language and the availability of varioustechnologies, their impact, their practical uses and the problems associated with the application of modern technological tools
Keywords: Modern technologies; enhancing speaking skill; applications